Arduino Based Voice Controlled Robotic Arm and Wheels (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present day world is all about various types of technology which as paved the way for multi-functional devices. The one application of technology is automation. Automation deals with technology, programs, robotics to achieve outcomes with minimal human input. Robotics include designing, construction, operation and use of robots. Most robots are used to do repetitive actions, work in hazardous environment and in medical fields too. This kind of robots can also be used in present pandemic situation. Here, a system is being proposed which is a robot with its arm and vehicle moving in a particular direction to place things from place to place. The movements of this robot is controlled using voice commands. The voice commands are received by the android application. The android application and the robotic wheels and arm are associated using a Bluetooth module. This voice commands are further processed using Arduino UNO. Arduino UNO which works as the brain to this project process the voice commands to perform suitable action.